Orexin receptors within the nucleus accumbens shell mediate the stress but not drug priming-induced reinstatement of morphine conditioned place preference - Qi, Keke; Wei, Chuguang; Li, Yonghui; Sui, Nan (Frontiers in Behavioral Neuroscience, 2013)
Orexins are recently found to participate in mediating stress-induced drug relapse. However, the neuroanatomical basis that orexin transmission modulates stress-induced drug seeking remains unknown. The nucleus accumbens shell (NAcSh), best known for its role in appetitive and negative motivation via dopamine receptors, is likely to be the potential important brain area where the orexin system mediates stress-induced drug relapse since the function of dopamine system in the NAcSh can be regulated by orexin transmission. In the present study, a morphine conditioned place preference (CPP) model was used to determine whether the two types of orexin receptors would be involved into footshock-induced and/or drug priming-induced CPP reinstatement differentially. The results showed that blockade of orexin-1 or orexin-2 receptor in the NAcSh significantly attenuated stress-induced morphine CPP reinstatement, but neither of the orexin antagonists had any effect on morphine priming-induced reinstatement. These findings indicate that the NAcSh is a brain area through which orexins participate in stress but not drug priming-induced relapse of opioid seeking.